Exploring space: ethical dilemmas for catholicism - Maurizio Balistreri (Frontiers in Space Technologies)
This article explores the Catholic Church’s perspective on space exploration and construction of human settlements beyond Earth, highlighting the significant moral dilemmas posed by these endeavors. While the Church generally supports space exploration, biotechnologies such as genome editing, assisted reproduction, and artificial wombs – technologies potentially essential for human survival and reproduction in space – clash with its moral principles. Non-therapeutic genetic modifications, regarded by the Church as an arbitrary redesign of human nature, are categorically prohibited. Similarly, assisted reproduction is considered morally unacceptable due to the destruction of embryos, the separation of the unitive and procreative aspects of human sexuality, and it fosters the selection of embryos and eugenics practices. Although the use of artificial wombs offers practical and safety benefits in space, it is also incompatible with the Church’s teachings on the dignity of human life and procreation. These conflicts underscore the Church’s challenge in reconciling humanity’s aspirations for space exploration with its ethical and spiritual framework. If technologies that fundamentally alter human nature or reproduction are excluded, the prospect of human expansion into space may remain morally unattainable.